Potensi Pengobatan Tradisional Umbul Klaten dalam mendukung Medical Wellness Tourism di Indonesia - Riskha Dora Candra Dewi (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
This research is to examine the use or application of traditional medicine introduced through tourism access regarding the potential of these treatments for medical wellness tourism in Indonesia. This research is a qualitative research with a holistic analytic approach. Namely, the approach to Water Meditation Therapy in Umbul Klaten as a unity of phenomena related to Medical Wellness Tourism. The research is field research with the main source directly to Umbul Klaten through researcher observation, interviews with several parties, and corroborated with documentation data. The results of the data are then analyzed inductively into a description that is easy to understand. This research reveals that traditional medicine in Umbul Klaten has great potential in supporting Medical Wellness Tourism in Indonesia. Treatment based on water meditation therapy at Umbul Brintik, Klaten, is proven to provide physical and mental health benefits, such as reducing stress, improving concentration, and helping spiritual balance. . In addition to health benefits, Umbul Klaten also has cultural and historical values that can be developed as a fitness and health-based tourism attraction. With the concept of Medical Wellness Tourism, tourists not only get a recreational experience but also holistic health therapy that combines traditional and modern medicine. However, there are still challenges in the development of this health tourism, such as regulation, service standardization, and marketing. Therefore, synergy between the government, community, and tourism industry players is needed to develop a sustainable Medical Wellness Tourism ecosystem. With the right strategy, Umbul Klaten has the potential to become a leading destination for health tourism in Indonesia.